Alguma coisa de desdizer - uma poética ás avessas: cacaso - Oliveira, Carlos Augusto Lima de (2006)
The aim of this study is to analyze the poet, composer, professor and reviewer Antônio Carlos de Brito’s artistic and intellectual path, mostly known as Cacaso. He was one of the most important authors and characters of the marginal generation in the seventies. Based on the idea of cultural resistance proposed by some authors concerning the action of some part of the Brazillian intellectuality in the period of militar dictatorship, this thesis investigates the role performed by Cacaso in the intellectual environment, and the way his poetic production is considered not only as a reflection, but also as a weapon of those resistance articulations. According to Michel de Certau’s ideas of tactics and resistances, this thesis analyzes the tactics elements assumed by Cacaso in the legitimation course of his generation as well as the elements presented in his poetry and the way they were revealing of those resistance tactics.